Why does the new disease activity score (EgyDAS) of Rheumatoid Arthritis not function? - Muravyev YV; Muravyeva LA; Glukhova SI; Litvinova MA (Rheumatica Acta: Open Access - Peertechz Publications, 2021)
The analysis of almost a century-long evolution of ideas about the criteria for the activity of Rheumatoid Arthritis showed that the developed complex indices for determination there of are far from perfect, in particular the Disease Activity Score 28 (DAS28), widely used in clinical practice [1]. Therefore, the recently developed new Disease Activity Score (EgyDAS) of Rheumatoid Arthritis [2] has attracted interest because it includes four laboratory markers of Rheumatoid Arthritis (RA) activity, as opposed to DAS28, which assesses only one laboratory marker.